2016
DOI: 10.1107/s2414314616005599
|View full text |Cite
|
Sign up to set email alerts
|

1-Benzyl-5-bromoindoline-2,3-dione

Abstract: In the title compound, C15H10BrNO2, the indoline ring system, the two ketone O atoms and the Br atom lie in a common plane, with the largest deviation from the mean plane being 0.073 (1) Å for the Br atom. The fused-ring system is nearly perpendicular to the benzyl ring, as indicated by the dihedral angle between them of 74.58 (10)°. In the crystal, molecules are linked by weak C—H...O hydrogen bonds and by π–π interactions [inter-centroid distance = 3.625 (2) Å], forming a two-dimensional structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The significance of isatin derivatives has even been extended to the design of novel anticancer drugs (Rodríuez-Argü elles et al, 2004), and recently, a number of isatin-based compounds have been reported to be inhibitors of caspase-3 and caspase-7 (Chu et al, 2007). As part of a continuing study on halogenated isatins (Kharbach et al, 2016a, Kharbach et al, 2016b, the structures of N-substituted derivatives of isatin have been reported using 1,3-dibromopropane (Qachchachi et al, 2016). Herein, we report the crystal structure of 5-bromo-1-(6-bromohexyl)indoline-2,3-dione, obtained using 1,6-dibromohexane as an alkylating agent as part of our work to develop new 5-bromoisatin derivatives.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…The significance of isatin derivatives has even been extended to the design of novel anticancer drugs (Rodríuez-Argü elles et al, 2004), and recently, a number of isatin-based compounds have been reported to be inhibitors of caspase-3 and caspase-7 (Chu et al, 2007). As part of a continuing study on halogenated isatins (Kharbach et al, 2016a, Kharbach et al, 2016b, the structures of N-substituted derivatives of isatin have been reported using 1,3-dibromopropane (Qachchachi et al, 2016). Herein, we report the crystal structure of 5-bromo-1-(6-bromohexyl)indoline-2,3-dione, obtained using 1,6-dibromohexane as an alkylating agent as part of our work to develop new 5-bromoisatin derivatives.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Isatin and its analogs are versatile substrates, which can be used for the synthesis of numerous heterocyclic compounds Sridhar & Sreenivasulu, 2001;Sarangapani & Reddy, 1994;Varma et al, 2004;Pandeya et al, 1999;Aboul-Fadl et al, 2010). In our work, we are interested in developing a new 5-bromoisatin and continuing the research work of Qachchachi to explore other applications (Qachchachi et al, 2013(Qachchachi et al, , 2014Kharbach et al, 2016). The present paper reports the synthesis and crystal structure of 5-bromo-1-methylindoline-2,3-dione (see Scheme).…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Many indole derivatives are under development as drug candidates due to their biological properties, which include antiviral, antitumor, antifungal, anti-angiogenic, anticonvulsant and antiparkinsonian activity (Sridhar, Muniyandy & Ramesh, 2001;Sridhar & Sreenivasulu, 2001;Sarangapani & Reddy, 1994;Varma et al, 2004;Pandeya et al, 1999;Aboul-Fadl et al, 2010). Continuing our work on the synthesis of new 5-bromoisatins and the study of their applications (Qachchachi et al, 2013(Qachchachi et al, , 2014Kharbach et al, 2016), we report herein on the synthesis and crystal structure of 5-bromo-1-nonylindoline-2,3-dione.The molecular structure of the title compound is illustrated in Fig. 1.…”
mentioning
confidence: 98%